(untitled) (Journal of Engineering, 2024)
Urban landscape analysis is crucial for understanding the dynamics of urban transformation, especially in historic city centers. This study delves into the morphological evolution of Baghdad, focusing on its transformation from a historic nucleus to a vast metropolitan area. The primary objective is to identify mechanisms of transformation that bring about changes in the structure of the town center. Utilizing a combination of geographical-morphological methods, historical maps, and modern satellite imagery, the research identifies six distinct urban growth patterns—concentric, irregular strip, scattered, multi-nuclei, sectoral, and instant growth. The research methodology includes a detailed collection of historical maps from Western geographical travelers of the 18th and 19th centuries and modern satellite images to compare historical and contemporary urban forms. Data digitization processes were employed to prepare these maps for analysis, followed by boundary determination to track Baghdad’s expansion over time. The study integrates these digital maps to conduct temporal analyses, characterizing the main morphological phases from the historical nucleus to modern urban growth. The study is able to set forth how a complex interplay of physical, social, economic, and political forces has defined the urban form of Baghdad. Findings will make it possible to understand these growth processes for modern urban planning and design. The management of sustainable growth in a way that tackles sprawl, connectivity, and human scale in design requires a fusion of historical contexts with modern practices. This study offers the necessary information and direction for sustainable urban development in Baghdad as well as any other historic town elsewhere.